High negative pressure subcutaneous suction drain for managing debilitating subcutaneous emphysema secondary to tube thoracostomy for an iatrogenic post computed tomography guided transthoracic needle biopsy pneumothorax: Case report and review of literature - Ahmed, Zeeshan (Int J Surg Case Rep, 2016)
INTRODUCTION: Subcutaneous emphysema is a common complication of tube thoracostomy. Though self-limiting, it should be treated when it causes palpebral closure, dyspnea, dysphagia or undue disfigurement resulting in anxiety and distress to the patient. PRESENTATION OF CASE: A 72 year old man who was a known case of COPD on bronchodilators developed a large pneumothorax and respiratory distress after a CT guided transthoracic lung biopsy done for a lung opacity (approx. 3 × 3 cm) at the right hilar region on Chest X-ray. Within 24 h of an urgent tube thoracostomy, patient developed intractable subcutaneous emphysema with closure of palpebral fissure and dyspnea unresponsive to increasing suction on chest tube. A subcutaneous fenestrated drain was placed mid-way between the nipple and clavicle in the mid-clavicular line bilaterally. Continuous negative suction (-150 mmHg) resulted in immediate, sustained relief and complete resolution within 5 days. DISCUSSION: Extensive and debilitating SE (subcutaneous emphysema) has to be treated promptly to relieve patient discomfort, dysphagia or imminent respiratory compromise. A variety of treatment have been tried including infraclavicular blow-hole incisions, subcutaneous drains +/− negative pressure suction, fenestrated angiocatheters, Vacuum assisted dressings and increasing suction on a pre-existing chest tube. We describe a high negative pressure subcutaneous suction drain which provides immediate and sustained relief in debilitating SE. CONCLUSION: Debilitating subcutaneous emphysema which causes distress, anxiety, palpebral closure, dyspnoea or dysphagia requires intervention. High negative pressure subcutaneous suction drain provides immediate and sustained relief in extensive and debilitating SE.